2010
DOI: 10.3945/ajcn.2010.29188
|View full text |Cite
|
Sign up to set email alerts
|

Survival predictability of lean and fat mass in men and women undergoing maintenance hemodialysis

Abstract: In MHD patients, higher FM in both sexes and higher LBM in women appear to be protective. The survival advantage of FM appears to be superior to that of LBM. Clinical trials to examine the outcomes of interventions that modify body composition in MHD patients are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 51 publications
6
54
1
3
Order By: Relevance
“…In contrast to obesity-related conditions, adipokine dysregulation in centenarians was uniquely associated with very low levels of leptin (less than 2.6 ng/mL) and low BMI, suggesting that age-related fat loss or lipoatrophy is major factor for adipose tissue dysfunction in centenarians. These findings are concordant with studies showing the protective functions of fat mass against morbidity and mortality in geriatric patients 45) and patients undergoing hemodialysis 46) . Although further studies focusing on the distribution of fat pads, adipocyte size and adipocyte metabolism in association with aging and age-related pathology are required, maintaining adipose tissue mass and function, particularly leptin signaling, seems to be indispensable for normal physiological functions under energy-deprived conditions, such as cachexia, or wasting syndrome, and chronic inflammation, which are associated with advanced aging.…”
Section: Human Data On the Adipose Tissue Phenotype In Centenarianssupporting
confidence: 82%
“…In contrast to obesity-related conditions, adipokine dysregulation in centenarians was uniquely associated with very low levels of leptin (less than 2.6 ng/mL) and low BMI, suggesting that age-related fat loss or lipoatrophy is major factor for adipose tissue dysfunction in centenarians. These findings are concordant with studies showing the protective functions of fat mass against morbidity and mortality in geriatric patients 45) and patients undergoing hemodialysis 46) . Although further studies focusing on the distribution of fat pads, adipocyte size and adipocyte metabolism in association with aging and age-related pathology are required, maintaining adipose tissue mass and function, particularly leptin signaling, seems to be indispensable for normal physiological functions under energy-deprived conditions, such as cachexia, or wasting syndrome, and chronic inflammation, which are associated with advanced aging.…”
Section: Human Data On the Adipose Tissue Phenotype In Centenarianssupporting
confidence: 82%
“…fat mass of 808 Japanese maintenance hemodialysis patients using dual-energy X-ray absorptiometry and revealed that higher fat mass index (kg/m 2 ) was related to lower mortality risk, especially noncardiovascular disease mortality (21). Noori et al and Huang et al reported similar results (22,23). They evaluated body fat mass measured by near -infrared interactance and triceps skinfold thickness, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…Actually, serum creatinine levels are considered to be unreliable as an indicator of muscle mass because they are dialysis dependent. However, in several studies, serum creatinine levels were found to be associated with lean body mass, confirming our findings (3,11,12). In the univariate correlation analysis, DMS was found to be strongly associated with both anthropometric measurements such as MAC and functions of the muscle mass defined by HGS.…”
Section: Discussionsupporting
confidence: 79%